Analisis Kualitas Layanan Website Erafone terhadap Kepuasan Pelanggan menggunakan E-S-Qual dan E-Recs-Qual - Nurul Syamsi Ekowati; Ari Kusyanti; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The number of businesses that operate on the internet by carrying out transactions through e-commerce continues to increase. The organization continues to try to reduce costs and increase productivity. Most of the companies will set up a website, which is considered as a new channel for conducting business transactions and customers can make purchases through the company's website. Service quality is the main factors for attracting more visitors in conducting visits and purchasing decisions on an e-commerce. To know the quality service of an e-commerce, it is necessary to conduct measurements of customer satisfaction. This research aims to know the quality of service the website Erafone towards customer satisfaction using the E-S-QUAL and E-RecS-QUAL which has been developed by Parasuraman. The constructs that build the research model used are: efficiency, fulfillment, system availability, privacy, responsiveness, compensation, contact, and satisfaction. A sample of 140 respondents was collected through an online questionnaire-based survey and analyzed using multiple linear regression. The results of this research show that the dimensions of efficiency, fulfillment, system availability, privacy, responsiveness, and contact affect customer satisfaction. The only factor that does not have significant influence towards customer satisfaction in using the services of the Erafone's website is compensation.